IMPROVING MOTIVATION OF LEARNING ENGLISH SUBJECT THROUGH INTEGRATION OF URBAN LEGEND LITERACY - A SHORT PLAY IN NARRATIVE TEXT OF TENTH GRADE STUDENTS AT SMAN 8 MALANG - Evi Maria K.; Prambudi Nur Adhitama (EDUCAFL : Journal of Education of English as Foreign Language, 2020)
This study aims at implementing integration teaching technique between Urban legend literacy with short-play in narrative text for educational purposes It uses as teaching strategies on improving students motivation and to raise further comprehension on important value of narrative text. The researh design was Classroom Action Research (CAR) design with qualitative approach. Interview guide, questionnaire, and rating scale were used as research instruments. The steps were planning, implementing observing, and reflecting. The participants of this study were tenth grade (X) students from the class of MIPA 6 and IPS 1 & 2 in SMAN 8 Malang. The data was analyzed qualitatively. Regarding the result of this present study, it is showed that this integration teaching technique was significantly effective and appropriate to be applied for tenth grade students, This technique also encourages students in discovering diverse range of National Urban Legend Literacy to be preserved. This study gave contributions in supporting English language learning in Indonesia, increasing the students’ motivation in learning English, and making the process of teaching and learning English becoming more interesting